Early satiety and postprandial fullness in gastroparesis correlate with gastroparesis severity, gastric emptying, and water load testing. Issue 4 (25th October 2016) - Parkman, H. P.; Hallinan, E. K.; Hasler, W. L.; Farrugia, G.; Koch, K. L.; Nguyen, L.; Snape, W. J.; Abell, T. L.; McCallum, R. W.; Sarosiek, I.; Pasricha, P. J.; Clarke, J.; et al.
Abstract: Background: Early satiety (ES) and postprandial fullness (PPF) are often present in gastroparesis, but the importance of these symptoms in gastroparesis has not been well‐described. The aims were: (i) Characterize ES and PPF in patients with gastroparesis. (ii) Assess relationships of ES and PPF with etiology of gastroparesis, quality of life, body weight, gastric emptying, and water load testing. Methods: Gastroparetic patients filled out questionnaires assessing symptoms (PAGI‐SYM) and quality of life (PAGI‐QOL, SF‐36v2). Patients underwent gastric emptying scintigraphy and water load testing. Key Results: 198 patients with gastroparesis (134 IG, 64 DG) were evaluated. Early satiety was severe or very severe in 50% of patients. Postprandial fullness was severe or very severe in 60% of patients. Severity scores for ES and PPF were similar between idiopathic and diabetic gastroparesis. Increasing severity of ES and PPF were associated with other gastroparesis symptoms including nausea/vomiting, satiety/early fullness, bloating, and upper abdominal pain and GERD subscores. Increasing severity of ES and PPF were associated with increasing gastroparesis severity, decreased BMI, decreased quality of life from PAGI‐QOL and SF‐36 physical health. Increasing severity of ES and PPF were associated with increasing gastric retention of a solid meal and decreased volume during water load test. Conclusions & Inferences: Early satiety and PPF are commonly severe symptoms in both diabetic and idiopathic gastroparesis. Early satiety and PPF severity are associated with other gastroparesis symptom severities, body weight, quality of life, gastric emptying, and water load testing. Thus, ES and PPF are important symptoms characterizing gastroparesis. ClinicalTrials.gov number: NCT NCT01696747.